Practicum E-Module Development to Improve Distance Learning Efficiency in Basic Physics Courses in the Pandemic Period - Metatia Intan Mauliana; Noly Shifiyah; Yunianita Rahmawati; Khoirun Nisa (Universitas Muhammadiyah Kalimantan Timur, 2022)
The Covid-19 pandemic has a broad impact on all sectors, including the education sector. Almost all learning from elementary to tertiary level (university) which was originally face-to-face has turned into distance learning (PJJ) or online. This study aims to see the effectiveness of online learning, especially in exact subjects. For example, in learning Basic Physics which has practical aspects, there are several problems during the pandemic, such as, 1) the limitations of the face-to-face implementation of the Basic Physics practicum during the pandemic, 2) the limitations and inconsistencies of conventional modules used in practicum implementation in distance education, and 3) The use of a Content Management System (CMS) in e-lerning that has not been maximized is an obstacle that requires immediate handling. Therefore, the researcher tried to develop a practicum e-Module using the Research & Development research method with the Rowntree development model collaborated with the Tessmer evaluation model. The results obtained in the study showed an increase in student positive motivation in doing independent practicum with the help of e-modules. The resulting E-module development can be said to have met the practical criteria, shown from the recapitulation of the percentage results of the questionnaire sheet assessment at the one-to-one stage of 84.66% and and the small group stage of 78.22%. The feasibility of the e-module that has been made is also quite good, seen from the validation results by the validator on the aspects of material, media, design and accessibility, on average, it is> 80%.